1990
DOI: 10.1111/j.1365-2621.1990.tb05193.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Natural Antioxidants in Frankfurters Containing Chicken and Pork

Abstract: Three natural antioxidant systems, tocopherol, extract of rosemary, a tocopherol and rosemary combination, and BHA/BHT were evaluated in frankfurters prepared from chicken and pork. Thiobarbituric acid numbers of refrigerated bulk and vacuum packaged samples stored in darkness for up to 18 days indicated that natural tocopherols provided significantly more protection than controls containing no antioxidant and were as effective as BHA/BHT in retarding oxidation. All bulkpackaged frankfurters except those conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 12 publications
5
28
0
1
Order By: Relevance
“…The power of rosemary extracts as antioxidants has been described in numerous reports 15, 37, 39–41. Our results are comparable with those obtained from the surface application of rosemary on rainbow trout,1, 42 horse mackerel or Mediterranean hake raw fillets,43 and those achieved from the incorporation of rosemary extract as an ingredient of beef patties 44.…”
Section: Resultssupporting
confidence: 88%
“…The power of rosemary extracts as antioxidants has been described in numerous reports 15, 37, 39–41. Our results are comparable with those obtained from the surface application of rosemary on rainbow trout,1, 42 horse mackerel or Mediterranean hake raw fillets,43 and those achieved from the incorporation of rosemary extract as an ingredient of beef patties 44.…”
Section: Resultssupporting
confidence: 88%
“…Recently many storage experiments were carried out to prove the antioxidative effects of plant materials and some of them investigated a considerable reduction in TBARS during the first part of the storage period. But generally at the end of the storage TBARS values had increased to values found in control samples (Wong et al 1995;Resurrecceccion and Reynolds 1990). Kulkarni et al (2011) reported similar results with precooked, frozen, reheated beef sausage treated with GSE.…”
Section: Changes In Povs During Frozen Storage Of Precooked Chicken Nsupporting
confidence: 57%
“…They reported no differences in TBA values and sensory scores between the two antioxidant treatments. Resurrection and Reynolds (1990) also found that OR was as effective as BHA/BHT in retarding lipid oxidation in chicken/pork frankfurters vacuum packaged and refrigerated 35 days.…”
Section: Lipid Stability During Refrigerated Storagementioning
confidence: 88%